UNLOCKING FINANCIAL WISDOM: EXPLORING DETERMINANTS OF FINANCIAL LITERACY AMONG UNIVERSITY STUDENTS - Sarah Sabir Ahmad; Azfahanee Zakaria; Nurdiyana Nazihah Zainal; Mhd Azmin Mat Seman (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Being able to fully grasp financial literacy is a criterion for an outstanding student. Making financial decisions would be difficult for a student with a low level of financial literacy. This will lead to troubles in making decisions for their future undertakings. To further evaluate the understanding of financial literacy level among university students, this research will focus on the factors affecting the level of financial literacy among the students in UiTM Kedah. It was conducted based on factors like self-exposure, family, and environment in helping the students’ further understanding of financial literacy. One hundred and six (106) students of UiTM Kedah were chosen as the respondents to answer the questionnaire. The data collected was analysed by the Statistical Package for the Social Sciences (SPSS) to help provide a better understanding of the research. According to the results, there is clear evidence between the independent variables and the level of financial literacy.